Thai Tourists Choice of Accommodation based on Marketing Behaviors in Vang Vieng Town, Lao People’s Democratic Republic - NONTHAPOT, Sakkarin (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019, 2019)
The objectives of this study are to determine 1) the opinions of Thai tourists on the choice of accommodation 2) the effect of Thai tourists’ staying decisions on the selection of accommodation based on marketing behavior in Vang Vieng Town, Vientiane Province, Lao People’s Democratic Republic (Lao PDR). The study employs a questionnaire as the tool to collect data from 430 Thai tourists who travel to Vang Vieng. The sampling method is convenience sampling with quota. The analysis employs Structural Equation Modelling (SEM) and ADANCO 2.1 software estimation. The results revealed that five paths were affected by the decisions of Thai tourists based on marketing, which directly affected 3 routes and indirectly affected 2 paths. The path from the Marketing Mix à Marketing Behavior is the path that was most affected by the decision of Thai tourists to choose based on the marketing mix factors. Therefore, the decision to choose accommodation, according to the marketing mix factors, have a direct positive relation with the behaviors of Thai tourists and affect accommodation selection decisions. In addition, entrepreneurs should determine suitable marketing strategies, especially human resource development.